Dynamics of rainfall pH in Passo Fundo, Rio Grande do Sul, Brazil - Cunha, Gilberto Rocca da; Santi, Anderson; Dalmago, Genei Antonio; Pires, João Leonardo Fernandes; Pasinato, Aldemir (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the dynamics of rainfall pH in Passo Fundo, RS, Brazil, from 1992 to 2007. The rainfall pH was monitored in 50 mL samples collected in a 10-cm diameter PVC tube connected to a rain gauge; samples were then stored in a freezer for later determination of pH. The dynamics of rain water pH was evaluated through the annual and monthly averages of the pH, the empirical probability of pH values distributed over the seasons, and the pH accumulated relative frequency. The rainfall events in Passo Fundo region have pH higher than the critical threshold (pH 5.6) to be considered acid rain. The analysis of a 16-year period showed reduction of the rainfall pH at 0.023 per year. Over that period, the average pH fell from 6.1 to 5.8. The rainfalls were slightly more acidic in the summer and spring than in the autumn and winter. In general, the analysis of rainfall events in the region showed no immediate risk of environmental acidification.